PERANCANGAN APLIKASI INVENTORY BARANG BERBASIS WEB MENGGUNAKAN METODE AGILE DEVELOPMENT di WARUNG ZULAIKHA - Risma, Ry; Hermawan, Arief (LPPM UNIVERSITAS BINA INSAN, 2024)
The inventory management system is an application specifically designed to assist in managing items in the warehouse of Warung Zulaikha. The previous item data recording system used at Warung Zulaikha was still considered ineffective as it was done manually. The process of recording stock in the warehouse was only written in a ledger, which is prone to errors and difficult to manage. Therefore, the purpose of developing this system is to provide computerized management of item data. This system is expected to make it easier for the shop owner to input, search, and manage item data more efficiently. To address this issue, this study creates an online inventory management system specifically designed for Warung Zulaikha using the Agile Development method. The system is developed using PHP, HTML, CSS, and JavaScript programming languages, with MySQL as the database. The results of this study show that this system can facilitate the shop owner in recording items and provide real-time and accurate stock reports at Warung Zulaikha.